A Study on Flouting Maxims in Divergent Novel - Ernawati Fitri; Laila Ulsi Qodriani (TEKNOSASTIK, 2016)
This research focuses on flouting maxim in Divergent novel which aim is to find the types and the function of flouting maxim. The researchers used descriptive qualitative research because the researchers strived to analyze and discusses the sentences of utterances which performs flouting maxim in Divergent novel. This research uses pragmatic approach which uses Grice’s theory of maxim. The result of this study shows that 21 data which are appropriated with the characteristic of flouting maxim. They consist of 12 flouting maxim of quantity, 2 flouting maxim of quality and 7 flouting maxim of relevance. Based on the data analysis the researchers concluded: the functions for flouting maxim of quantity are to explain more about topic, to stress something and unwillingness to cooperate; the functions for flouting maxim of quality are to show panic, to convince the addressee and to hide something; the functions for flouting maxim of relevance are to change the topic of conversation and to avoid talking about something.